O papel da gestão no desempenho dos fundos de investimento imobiliário no Brasil (2010-2016) - Weiss, Leila Aparecida Scherer (2017)
Among the investment options available on the market, there is highlight to the real estate investment funds, which allow small investors to invest in projects previously restricted to large investors and large developers, thus representing an interesting alternative of long-term financing, making it accessible to all investors. However, performance assessment of these funds, which would take into consideration their management, as well as a comparison with for rental real state investment, is an area of study still underexplored, which requires more investigation. Therefore, the overall objective of this study is to identify how management influences the performance of IFIs, compared to direct leaseholds in the period from 2010 to 2016. The theoretical framework contemplates the aspects inherent in the Modern Theory of Portfolio and Agency Theory. The study also includes real estate investments with emphasis on Real Estate Investment Funds, types, advantages, and risks of investment. The methodology used is the hypothetical-deductive, and it is classified, regarding the research problem as, quantitative; as for the objectives, it is exploratory and descriptive and as for the procedures, it is bibliographical and documentary. The results indicate that the performance of the funds is directly linked to the management of these funds, due to the policies adopted by each of the managers. It is also noteworthy that, in comparison to direct investment in real estate, real estate investment funds present higher returns for investors.